Narrating resistance: the memory of trauma in A trilha dos ninhos de aranha and “Lembrança de uma batalha”, by Italo Calvino - Ferraz, Bruna Fontes (2012)
In this article we aim to present the engaged writing of Italo Calvino (1923-1985), through which he had sought to represent his own experiences as a soldier of Resistenza against the italian fascism. In order to do this, we’ll consider both his first novel A trilha dos ninhos de aranha (1947), and his tale “Lembrança de uma batalha” (1974), which is in his posthumous work O caminho de San Giovanni (2000). So we’ll discuss the way Calvino relate his memories and traumas as a soldier of Partigiani movement (italian warriors that fought against Nazi-Fascism during the Second World War), under a child’s vision, as it happens in his first novel whose theme is the War itself but under an indirect look; as well as in his tale, in which Calvino resort to his memories, which seem so many times imagined, to recompose his way back to the village of Baiardo. In this sense, we’ll observe both how the literary writing is the way Calvino has found to go back to the source of Memory, and how his whole personal fighting to recall and overcome the gaps of his memory so that Calvino becomes able to remember and even narrate his own pain.